Inferential and predictive modelling of transition success in dairy cows on automatic milking systems - Hannon, Fergus (2025)
The health and welfare of the transition cow impacts the economic, environmental and social sustainability of the dairy industry. Despite significant improvements in our understanding of the physiological challenges this period poses, limited improvement in the morbidity and mortality rates associated with transition have been reported in the